Pendekatan, Strategi dan Teknik Bimbingan Konseling dalam Mengatasi Permasalahan Sosial Remaja - Annida Aulia Sholehah; Tsana Nurul Azizah; Hidayat Nurwahid Sinurat (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This article aims to find out what approaches, strategies and techniques for guidance and counseling are good and correct in dealing with adolescent social problems. This research was conducted using qualitative methods, where researchers distributed forms containing questions to respondents. In this research, there were two respondents who were the targets of the research, namely high school students and guidance and counseling teachers. The data collection method that the researcher took was the method of non-participant observation and literature review, where the observer was outside the subject being studied and did not participate in the activities they carried out. This research measures all the domains that exist in students in dealing with personal, social, learning and career problems, and their relationship with how a teacher knows the behavior of each individual in the learning process. So that a teacher can direct his students to be able to face every problem. The results of this research explain that a student initially has a high level of trust in providing counseling to a counseling teacher at their respective school, but not all of these teachers have a good impact on students who do counseling. There are still many guidance and counseling teachers who do not know how to respond and how to communicate well with the students who are counseling with them. And then this creates a feeling of discomfort for students so that they no longer have a sense of trust in the guidance and counseling teacher.